Harmonisasi Identitas Destinasi: Tantangan Komunikasi Pariwisata Pemerintah dalam Branding Badung The Soul of Bali - Ni Luh Putu Widya Astuti; Ni Made Prasiwi Bestari (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
The branding “Badung The Soul of Bali” was introduced as a unified tourism identity; however, its implementation reveals contradictory patterns and uneven representation across regions. This study aims to analyze how government-led tourism communication operates through visual, marketing, and managerial dimensions, while identifying perceptual gaps between the ideal image promoted and the actual experiences of tourists. A qualitative descriptive approach was employed through in-depth interviews with government actors, tourism industry operators, and domestic and international tourists, supported by digital content observation and source triangulation to strengthen data validity.The findings highlight several striking contradictions. International tourists perceived the official logo as a “general Bali branding” rather than a representation of Badung, indicating weak destination differentiation. Premium hotels also refrained from using the logo, arguing that it does not align with their luxury-oriented visual identity. In marketing communication, official government content performed significantly worse than traveler-generated videos; despite showcasing the same attractions, traveler content achieved much higher engagement due to its authenticity, emotional appeal, and personal storytelling. At the managerial level, the stark disparity between South Badung and North Badung created a destination image gap, where the harmonious identity promoted through branding does not match on-site realities, generating the risk of over-promising. This study recommends developing a dedicated sub-branding for North Badung to authentically represent its distinct landscape and cultural characteristics. Furthermore, the government is advised to provide collaborative incentives for hotels and tourism businesses that adopt the “The Soul of Bali” logo, thereby strengthening stakeholder coordination and ensuring greater alignment between the communicated image and the destination reality.